Mathematical wondrous in the al-Quran through surah al-Alaq - Ishak, Nur Dalila; Kilicman, Adem; Said Husain, Sharifah Kartini; Din, Rosseni (Fakulti Pendidikan, Universiti Kebangsaan Malaysia, 2017)
This paper demonstrates how numerical truths inherent between Surah Al Alaq and Al-Quran based on Bediuzzaaman Said Nursi ideas. The Surah Al Alaq is the first surah that was revealed to our Prophet Muhammad (SAW). Thus, we study and showed the mira culousness that happens on how by only the first time surah Al Alaq been revealed to Prophet Muhammad (SAW), it already portrays the geometric map as pattern of Al-Quran even though manuscript of Al-Quran not even exists during that time. This study hopefully can show the wondrous of the Al-Quran and also awareness and the greatness of Al-Quran.